A d10 Ag(I) amine–borane σ-complex and comparison with a d8 Rh(I) analogue: structures on the η1 to η2:η2 continuum - Johnson, A; Martinez-Martinez, A; Macgregor, S; Weller, A (Royal Society of Chemistry, 2019)
H3B·NMe3 σ-complexes of d8 [(L1)Rh][BArF4] and d10 [(L1)Ag][BArF4] (where L1 = 2,6-bis-[1-(2,6-diisopropylphenylimino)ethyl]pyridine) have been prepared and structurally characterised. Analysis of the molecular and electronic structures reveal important but subtle differences in the nature of the bonding in these σ-complexes, which differ only by the identity of the metal centre and the d-electron count. With Rh the amine–borane binds in an η2:η2 fashion, whereas at Ag the unsymmetrical Ag⋯H3B·NMe3 unit suggests a structure lying between the η2:η2 and η1 extremes.